Kepemimpinan Situasional dalam Pendidikan Anak Usia Dini: Strategi Peningkatan Kompetensi Guru - Juniawati, Rinta; Arifin, Imron; Sutarno, Sutarno (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Situational leadership is increasingly gaining attention in early childhood education, where the role of teachers is crucial in laying the foundation for children's development. This paper presents findings from a literature review aimed at exploring the concept of situational leadership and its implementation approaches in enhancing teachers' competencies in early childhood education. The research method involves searching for and analyzing relevant articles from scientific databases, including more than 20 articles reviewed using thematic analysis techniques. This approach explores the concept of situational leadership and strategies for improving teacher competence based on the literature. Findings from the literature highlight the relevance of situational leadership in addressing the complexity of classroom dynamics and the individual needs of children. The reviewed articles identify several strategies involving the use of situational leadership, such as understanding children's needs, adjusting instruction, providing individual support, and fostering collaborative mentoring. The implications of these findings suggest that applying the concept of situational leadership can have a positive impact on enhancing teacher competence and the quality of learning in early childhood education institutions.